2014
DOI: 10.1073/pnas.1413570112
|View full text |Cite
|
Sign up to set email alerts
|

Sound credit scores and financial decisions despite cognitive aging

Abstract: Age-related deterioration in cognitive ability may compromise the ability of older adults to make major financial decisions. We explore whether knowledge and expertise accumulated from past decisions can offset cognitive decline to maintain decision quality over the life span. Using a unique dataset that combines measures of cognitive ability (fluid intelligence) and of general and domain-specific knowledge (crystallized intelligence), credit report data, and other measures of decision quality, we show that do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
124
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(143 citation statements)
references
References 32 publications
(25 reference statements)
13
124
3
Order By: Relevance
“…The SOEP, for instance, relies almost exclusively on self-report assessments of behavior rather than on observational or registry data. Recent studies have shown the feasibility of complementing self-report assessments with objective real-world assessments, such as health markers (Moffitt et al, 2011) or financial reports (Li et al, 2015). Showing predictive value of current risk-taking propensity measures for real-world behavior would remove potential doubts about the validity of the single-item measures in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The SOEP, for instance, relies almost exclusively on self-report assessments of behavior rather than on observational or registry data. Recent studies have shown the feasibility of complementing self-report assessments with objective real-world assessments, such as health markers (Moffitt et al, 2011) or financial reports (Li et al, 2015). Showing predictive value of current risk-taking propensity measures for real-world behavior would remove potential doubts about the validity of the single-item measures in the present investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Third, it is also possible that older adults have learned from experience with previous life decisions that striving for the very best poses threats to their emotional well-being that they are motivated to avoid. Indeed, it has been argued that older adults may have learned insights relevant to decision making from life experience (Bruine de Bruin, Strough, & Parker, 2014; Li, Baldassi, Johnson, & Weber, 2013; Li, Goa, Enkavi, Zaval, Weber, & Johnson, 2015; Yates & Patalano, 1999). …”
Section: Discussionmentioning
confidence: 99%
“…Recently, theorists have built upon classic observations of adult age differences in fluid and crystallized cognitive abilities 130 to explain age-related differences in decision performance 97,131,132 . Although fluid cognitive ability decreases linearly across adulthood, crystallized ability increases non-linearly and begins to level off in late middle age 131 (see figure, panel a).…”
Section: Functional Chemical and Structural Circuit Characteristicsmentioning
confidence: 99%